Mechanisms underlying the early phase of spike frequency adaptation in mouse spinal motoneurones - Miles, GB (Blackwell Science Inc, 2005)
Spike frequency adaptation (SFA) is a fundamental property of repetitive firing in motoneurones (MNs). Early SFA (occurring over several hundred milliseconds) is thought to be important in the initiation of muscular contraction. To date the mechanisms underlying SFA in spinal MNs remain unclear. In the present study, we used both whole-cell patch-clamp recordings of MNs in lumbar spinal cord slices prepared from motor functionally mature mice and computer modelling of spinal MNs to investigate the mechanisms underlying SFA. Pharmacological blocking agents applied during whole-cell recordings in current-clamp mode demonstrated that the medium AHP conductance (apamin), BK-type Ca(2+)-dependent K(+) channels (iberiotoxin), voltage-activated Ca(2+) channels (CdCl(2)), M-current (linopirdine) and persistent Na(+) currents (riluzole) are all unnecessary for SFA. Measurements of Na(+) channel availability including action potential amplitude, action potential threshold and maximum depolarization rate of the action potential were found to correlate with instantaneous firing frequency suggesting that the availability of fast, inactivating Na(+) channels is involved in SFA. Characterization of this Na(+) conductance in voltage-clamp mode demonstrated that it undergoes slow inactivation with a time course similar to that of SFA. When experimentally measured parameters for the fast, inactivating Na(+) conductance (including slow inactivation) were incorporated into a MN model, SFA could be faithfully reproduced. The removal of slow inactivation from this model was sufficient to remove SFA. These data indicate that slow inactivation of the fast, inactivating Na(+) conductance is likely to be the key mechanism underlying early SFA in spinal MNs.